ChemInform Abstract: Zinc‐Catalyzed Dehydrogenative Cross‐Coupling of Terminal Alkynes with Aldehydes: Access to Ynones. Issue 17 (April 2016) - Tang, Shan; Zeng, Li; Liu, Yichang; Lei, Aiwen
Abstract: The title reaction used α, α, α‐trifluoroacetophenone as oxidant and Zn(OTf)2 as catalyst.